AB1200 From the calcaneus quantitative ultrasonography (QUS) to the femoral radiofrequency echographic multi spectrometry (REMS): non-ionising approaches to diagnosize osteoporosis proposed by f.i.r.m.o. foundation. (12th June 2018) - Cavalli, L.; Cianferotti, L.; Giusti, F.; Gronchi, G.; Pisani, P.; Brandi, M.L.
Abstract : Background: The high prevalence of osteoporosis and its insidious development, often silent until a fracture occurs, make it necessary to resort to prevention by promoting early diagnosis and educational programmes for a healthy life style. Objectives: To develop screening campaigns of the Italian population for the osteoporosis prevention thanks to the collaboration with F.I.R.M.O. Foundation (Fondazione Italiana Ricerca Malattie Ossee). 1 Methods: An experienced medical staff administered to the afferent people the IOF "One minute risk test" questionnaire, (to detect the presence of clinical risk factors), together with a densitometric examination performed by a portable device aboard a mobile unit, in several Italian cities between 2011 and 2017. The technique employed to assess bone status in 2011 and 2012 was calcaneus Quantitative Ultrasonography (QUS), applied to a peripheral skeletal site, which has been shown as effective in identifying osteoporotic men or post-menopausal women. 2 Although representing a low-cost and accessible approach, the heel measurement of speed of ultrasound (SOS) can be influenced by foot positioning, oedema and temperature. 3 Since 2017, a novel non-invasive densitometric technique is available, which allows to evaluate the axial fragile bone sites (spine and femur). It is Radiofrequency Echographic Multi Spectrometry (REMS), that a multicentric clinical study has been shown to provide parameters highly correlated with DXA ones. Results: As measured by calcaneus QUS in 7305 subjects, the prevalence rate of osteoporosis was approximately 18.7%, while the 42.6% had a T-score compatible with osteopenia. People with a QUS T-score <−2.5 was recommended to early undergo a DXA at lumbar and femoral sites and a specialistic visit. On the other hand, REMS examinations at femoral neck, performed on 397 people, revealed that osteoporosis resulted in 25% of the sample and osteopenia in 54%. Also in this case, people with a T-score <−2.5 was suggested to perform a DXA, considering that the accuracy and operator-independent automatic analysis performed by REMS, make more reliable the obtained data. Conclusions: Nowadays, with REMS introduction, F.I.R.M.O. foundation and the health system could avail themselves of a new non-invasive, rapid, easy-to-use and automatized technology for the prevention of osteoporosis. References: [1] Cavalli L, Guazzini G, Cianferotti L, et al. "Prevalence of osteoporosis in the Italian population and main risk factors: results of BoneTour Campaign". BMC Musculoskeletal Disorders (2016) 17:396; DOI 10.1186/s12891–016–1248–8 [2] Krieg MA, Barkmann R, Gonnelli S, Stewart A, Bauer DC, Del Rio Barquero L, et al. Quantitative ultrasound in the management of osteoporosis: the 2007. ISCD official positions. J Clin Densitom. 2008;11:163 [3] Hans D, Krieg MA. Quantitative ultrasound for the detection and management of osteoporosis. Salud Publica Mex2009;51suppl 1:S25-S37 Acknowledgements: The authors are grateful to F.I.R.M.O. Foundation for promoting these screening campaigns. Disclosure of Interest: None declared